Air Pollution and Daily Hospital Admissions for Cardiovascular Diseases in Windsor, Ontario - Fung, Karen Y. (Springer International Publishing, 2005)
OBJECTIVE: To examine the role that ambient air pollution plays in exacerbating cardiovascular disease hospitalization in Windsor, Ontario. METHODS: The number of daily cardiac hospital admissions was obtained from all Windsor hospitals from April 1, 1995 to December 31, 2000 and linked to concentrations of ambient air pollutants and weather variables. The logarithm of daily counts of hospitalization was regressed on the levels of pollutants, after adjusting for seasonal, weekly cycles, and weather variables using time series analysis with natural splines as smoothing functions. RESULTS: Of all the pollutants considered, sulphur dioxide (SO(2)) had the strongest effect on cardiac hospitalization among the >65 age group. The percentage increase in daily admission was 2.6% for current day sulphur dioxide level (95% CI: 0.5-6.4), 4.0% for 2-day mean level (95% CI: 0.1-6.9), and 5.6% (95% CI: 1.5–9.9) for 3-day mean level for an increase in interquartile range of 19.3 ppb. When particulate PM(10) was included in the model, the contributing effect of sulphur dioxide remained significant for the >65 age group for all three levels. CONCLUSIONS: Short-term effects of sulphur dioxide are associated significantly to daily cardiac hospital admissions for people >65 years of age living in Windsor. Since Windsor is a border city, additional monitoring and assessment is recommended to determine if air quality and resultant health effects have deteriorated since traffic congestion at the border has increased following the events of September 11, 2001.